Situation Report: Romania, 8 February 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian Foreign Minister Visits Bucharest / by Anneli Maier Ties with Nicaragua / by Paul Gafton Power Shortages / by Dan Ionescu Poetry and Truth, Romanian Style / by Crisula Stefanescu Scratching the Surface of Daily Life / by Crisula Stefanescu